Alterations in Interleukin-6 and Other Parameters during Open-Heart Surgery - Chultemdarjaa, Tuvjargal; Ganbaatar, Undarmaa; Batjargal, Sodgerel; Nachin, Baasanjav; Artbazar, Bayarzaya; Dansran, Purevsuren (Central Asian Journal of Medical Sciences, 2017)
Objectives: Cardiopulmonary bypass (CPB) using a heart-lung machine to perform open-heart surgery is known to be associated with numerous pathophysiologic changes in body systems. Soon after beginning extracorporeal circulation, an activation process of certain plasma protein systems occurs as blood contacts the foreign surfaces of the cardiopulmonary bypass circuit. During cardiac surgery with CPB, there is a systemic inflammatory reaction involving an enhanced release of inflammatory cytokines. In this study, we investigated the occurrence of systemic inflammatory response syndrome (SIRS) and the mechanisms that lead to the protraction of SIRS in patients who are operated under CPB. Methods: Blood samples from 27 patients (12 females and 15 males, aged 18-63 years) who underwent CPB were collected before and at several time points after surgery and analyzed for plasma levels of proinflammatory cytokines and white blood cells (WBC). Results: In patients with SIRS, the duration of CPB, interleukin-6 (IL-6) count, and WBC count after aortic declamping were significantly higher. The occurrence of SIRS was significantly correlated with the highest recorded level of IL-6 (OR 1.01, 95% CI 1.00-1.01, p<0.05) and the duration of CPB (r = 0.578, p<0.001). Conclusion: The study findings suggest that the duration of CPB and cytokinemia characterized by high IL-6 levels may play an important role in the development of the SIRS.